Trends in Infant Mortality Rate and Policy Impact in India: A Systematic Assessment - Sharma, Shivam; Gopi, Jaychandran; Nandy, Shounak; Khushi, Khushi; Kumar, Nitesh (Journal of Neonatal Surgery, 2025)
Background: Infant Mortality Rate (IMR) is a pivotal indicator of health systems. This study systematically assesses IMR trends in India (1995–2020) and Jammu & Kashmir, correlates them with national programmes (e.g., NRHM, JSY, Mission Indradhanush), and contextualizes findings via NFHS equity analyses and the Ballabgarh project case study. Methods: Annual IMR data were analyzed using LOESS smoothing and linear regression. Equity trends were evaluated via NFHS‐1 to NFHS‐4 data [5]. The Ballabgarh project outcomes (1972–1997) were reviewed [6]. Model fit was assessed by R². Results: IMR declines (per year) were India Total −1.685, Rural −1.983, Urban −1.000, J&K −1.769 (R² ≥ 0.996). Equity gaps narrowed post-NHM but persisted for SC/ST and poorest quintiles. The Ballabgarh project demonstrated a significant reduction in neonatal mortality rates over the study period, indicating the effectiveness of a focused primary healthcare intervention and stands as strong evidence that neonatal mortality can be reduced to Kerala-like levels independent of socioeconomic development. These outcomes suggest that localized, sustained interventions can achieve substantial improvements in neonatal health outcomes, potentially serving as a model for similar rural healthcare programs across India. Conclusion: Coordinated policy interventions drove sustained IMR reduction. Targeted rural schemes and equity-focused strategies are crucial. Lessons from NFHS and Ballabgarh guide future programme refinements.